How Are Traditional Chinese Opera and Drama Integrated into Fiction?—An Analysis Based on Chen Yan’s Novels The Comedy and The Protagonist - WU Yiqin (Frontiers of literary studies in China, 2023)
Chen Yan’s novels are steeped in traditional Chinese culture. The Comedy and The Protagonist draw on and use traditional national art resources such as Chinese opera and drama to discover anew and create “tradition” from a modern perspective. Traditional Chinese opera and drama shape the narrative aesthetic nature of Chen Yan’s novels both explicitly and implicitly. The difference between opera and drama, lyrical and impressionistic style, and narrative and action also forms its diverse narrative aesthetic style. The origin and distinction of style and form between Chen Yan’s novels and traditional Chinese comedies and modern Chinese novels are profoundly influenced by time and history, which essentially determines the spiritual structure and narrative aesthetic of Chen Yan’s novels.